Corticosteroid Therapy in COVID-19 Associated With In-hospital Mortality in Geriatric Patients: A Propensity Matched Cohort Study. Issue 7 (8th April 2022) - Lidou-Renault, Valentine; Baudouin, Edouard; Courtois-Amiot, Pauline; Bianco, Celine; Esnault, Hélène; Rouet, Audrey; Baque, Margaux; Tomeo, Charlotte; Rainone, Antonio; Thietart, Sara; Veber, Romain; Ayache, Clementine; et al.
Abstract: Background: Few data are available on the prognosis of older patients who received corticosteroids for COVID-19. We aimed to compare the in-hospital mortality of geriatric patients hospitalized for COVID-19 who received corticosteroids or not. Methods: We conducted a multicentric retrospective cohort study in 15 acute COVID-19 geriatric wards in the Paris area from March to April 2020 and November 2020 to May 2021. We included all consecutive patients aged 70 years and older who were hospitalized with confirmed COVID-19 in these wards. Propensity score and multivariate analyses were used. Results: Of the 1 579 patients included (535 received corticosteroids), the median age was 86 (interquartile range 81–91) years, 56% of patients were female, the median Charlson Comorbidity Index (CCI) was 2.6 (interquartile range 1–4), and 64% of patients were frail (Clinical Frailty Score 5–9). The propensity score analysis paired 984 patients (492 with and without corticosteroids). The in-hospital mortality was 32.3% in the matched cohort. On multivariate analysis, the probability of in-hospital mortality was increased with corticosteroid use (odds ratio [OR] = 2.61 [95% confidence interval (CI) 1.63–4.20]). Other factors associated with in-hospital mortality were age (OR = 1.04 [1.01–1.07], CCI (OR = 1.18 [1.07–1.29], activities of daily living (OR = 0.85 [0.75–0.95], oxygen saturation < 90% on room air (OR = 2.15 [1.45–3.17], C-reactive protein level (OR = 2.06 [1.69–2.51], and lowest lymphocyte count (OR = 0.49 [0.38–0.63]). Among the 535 patients who received corticosteroids, 68.3% had at least one corticosteroid side effect, including delirium (32.9%), secondary infections (32.7%), and decompensated diabetes (14.4%). Conclusions: In this multicentric matched-cohort study of geriatric patients hospitalized for COVID-19, the use of corticosteroids was significantly associated with in-hospital mortality.